KEUTUHAN NATURE-HAKEKAT ALLAH-MANUSIA DI DALAM PRIBADI YESUS KRISTUS TUHAN - Sumanti, Joubert (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2020)
The wholeness of the nature of God-Man in the Person of Jesus Christ the Lord. This thought is the subject of research to understand who Jesus is. The subject of this research arises because of the development of understanding or discussion both internally in STTIndonesia and in the organization of Baptist churches in Manado. The discussion that developed was about the actions and words of Jesus while He was on earth, say thirty-three years when He humbled Himself. (Phil 2: 6-7). The initial stage puts forward the Old Testament and the New Testament. The Old Testament is a book of God's people that outlines the framework of God's plan (Father, Son, and Holy Spirit), which foretells the coming of a release for God's people whose fulfillment to a new age. The New Testament tells of the fulfillment of the Old Testament only in Jesus Christ the Lord. In particular the four Gospels, four versions of the existence and ministry of Jesus on earth were emphasized. The next stage outlines aspects of Jesus 'deity and Jesus' humanity. This description is based on examining and exposing several passages from Paul's writings. Both of these nature are in the person of Jesus Christ the Lord. Both of these realms are intact in the sense of hypostatic union, wholeness that does not blend, mingle, merge, but still maintain each other's existence in the one person of Jesus Christ the Lord. The next stage outlines pre-existence, service, death-resurrection, and ascending to heaven surveyed in the book of John. The goal is on the basis of hypostatic union in the person of Jesus, then the entire scope of life, service, in deeds and words, all done in one person or person of Jesus Christ God. The deeds and words of Jesus did not occur or were done because of the nature or nature of his God or man, but all those actions in one person or person of Jesus Christ the Lord. So, those who teach, heal, make things spectacular, cry, thirsty, hungry, moved by compassion, even crucified, die-rise from the dead are the persons of the Lord Jesus Christ. John Stott, in The Authentic Jesus states that Chalcedonian Christology is the only perfect synthesis of biblical data. In fact, the expression of the two nature-essence in one Person is more than the synthesis of the New Testament; the phrase is the foundation of the New Testament documents (cf. Mk 13:32).